Literature in Protestant England, 1560-1660 - Sinfield, Alan (Routledge revivals., 2009)
The hardline, uncompromising theology preached by the English Church in the 16th and 17th Centuries had disturbing effects on the literature of the period. This study, originally published in 1983,€assesses the importance of the prevailing religious climate to the work of several major writers, both in and out of sympathy with the contemporary protestantism. It is argued that the accepted view of the period€as essentially 'Christian-Humanist' obscures the harsher aspects of a Calvinism which throws into relief the agonies of a writer like Donne, the acceptances of one like George Her.